Covering digital health applications in the public insurance system: how to foster innovation in patient care while mitigating financial risks—evidence from Germany - Groene, Nicole; Schneck, Luca (Frontiers in Digital Health, 2023)
Context: Digital health applications that support patients in managing their condition can have a positive impact on patients’ health and improve the overall care process. In late 2019, as the first country worldwide, Germany included digital health applications in the benefit basket of the Statutory Health Insurance system to enable fast, broad-scale patient access and encourage innovation in the digital health industry. While the policy is widely recognized as a pioneering step toward improving patient care through digital technologies, there are concerns regarding the mechanics of the policy and the resulting financial risks for the statutory health insurance system. Goals: The primary objective of this article is to provide a comprehensive and balanced overview of the German policy by evaluating its success in achieving its goals and by reviewing challenges that have emerged. The secondary objective is to delineate prospective policy options and areas warranting future research. Approach: The article analyzes publicly available data of the Federal Institute for Drugs and Medical Devices collected between February 1st and July 17th, 2023, and complements it with empirical findings published by academic institutions and sickness funds. It discusses policy options and related areas of future research to overcome the identified challenges without jeopardizing the purpose of the legislation to encourage innovation in the digital health industry to improve patient care. Conclusion: In line with the goals of the reimbursement policy, the inclusion of digital health applications in the SHI benefit basked has entailed new digital treatment options for patients across multiple disease areas. However, from a health policy perspective, the policy has several shortcomings, including low prescription rates, the temporary reimbursement of digital health applications that lack proven benefit, and a pricing framework that does not take into account the efficacy and efficiency of a treatment and may lead to a suboptimal allocation of public resources. Rather than the public system covering digital health applications without proven benefit, the authors suggest giving SHI organizations more budget authority to directly incentivize research and development activities and to introduce value-based pricing. More research is needed to determine the details of these mechanisms.